BS EN IEC 63171-6. Connectors for electrical and electronic equipment. Part 6. Detail specification for 2-way and 4-way (data/power), shielded, free and fixed connectors for power and data transmission with frequencies up to 600 MHz (22nd January 2021) - British Standards Institution
No abstract available